Pengaruh Kepuasan Gaji, Beban Kerja dan Motivasi Kerja terhadap Turnover Intention Karyawan Produksi - Prayitno, Ronaa Salma Putri; Hartono, Sri; Chamidah, Siti (Forum Kerjasama Pendidikan Tinggi, 2025)
High employee turnover intention can be detrimental to the company because it results in wasted recruitment and training costs. One of the factors that influence turnover intention is salary satisfaction, workload, and work motivation. This study aims to determine and explain the effect of salary satisfaction, workload, and work motivation on the turnover intention of production employees at PR Alfi Putra Trenggalek. This study uses a quantitative approach with a population of 407 production employees and a sample of 80 respondents taken using a simple random sampling technique. Data analysis was carried out using Structural Equation Modeling (SEM) with the help of Smart Partial Least Squares (PLS) software version 4.0.9.6. The results showed that salary satisfaction had a negative and significant effect on employee turnover intention (p <0.05), workload had a positive and significant effect on turnover intention (p <0.05), and work motivation had a negative and significant effect on turnover intention (p <0.05). In other words, the higher the salary satisfaction and work motivation, the lower the employee turnover intention, while a high workload actually increases turnover intention. Based on the interview results, it is known that dissatisfaction with salary is caused by an uncertain payment system because it uses a piecework system. The conclusion of this study is that companies need to evaluate the salary system and workload management to reduce turnover intention and increase employee retention.